Bowling psychology - Hinitz, Dean R. (Champaign, IL Human Kinetics, 2016)
As the leading authority on bowling's mental game, Dean Hinitz has worked with the premier players, coaches, and teams in the sport. He has helped countless pros elevate their results, avoid slumps, and overcome stressors affecting performance. He has improved their play, and now he's ready for you. In Bowling Psychology, you'll learn the mental strategies for performing your best, day in and day out. From progressive muscle relaxing techniques to positive self-talk and focus cues, you will pick up spares more consistently, improve accuracy, and overcome anxieties. In addition to a foreword written by 2015 PBA Player of the Year Jason Belmonte, Bowling Psychology features insights, advice, and anecdotes from bowling's best. Manage pressure, find your focus, and reach your potential. With detailed information on topics including mindfulness training, sensory awareness, and the mind-body connection, Bowling Psychology is your all-in-one toolbox for mental mastery of the lanes.
Chapter 1 Goal Setting and Self-Assessment -- Chapter 2 Thinking Like a Champion -- Chapter 3 Establishing Your Preshot Routine -- Chapter 4 The Shot Cycle: One Shot for the Money -- Chapter 5 Toughness to Overcome Adversity -- Chapter 6 Mental Secrets to Making Spares -- Chapter 7 Raising Peaks and Filling Valleys -- Chapter 8 Team Building -- Chapter 9 Coaching and Raising a Champion -- Chapter 10 Putting It All Together to Play Boldly
"Revised edition of Focused for bowling, published in 2003."
Includes bibliographical references (pages 224-225) and index.
Keywords: Bowling -- Psychological aspects; Bowling -- Coaching